A Comparative Analysis of Risk Culture in Financial and Non-Financial Firms - Albinali, Noora (2017)
The following study explores risk culture by incorporating viewpoints from publications that cover: risk management, leadership, communication, employee motivation and satisfaction, and learning organisations. The aspiration of the study is to determine whether a distinction between risk culture in financial and non-financial industries in Bahrain exists, and clarify the possible reasoning behind any detected variation. Together with identifying any apparent weak or strong risk culture due to the general culture in the Middle East. The contribution of the study is to provide a tool to assess risk culture between and within, financial and nonfinancial institutions. Additionally, the paper brings to light the lack of risk-awareness in the middle east due to poor perceptions towards the concept of risk culture. At present, papers depict risk culture as a relatively new concept in the financial industry, compared to the non-financial industry. Forming the assumption that firms operating in the non-financial industry have a generally ‘stronger’ risk culture than financial industry firms. As such, academic and practice literature state that financial firms can benefit from incorporating non-financial firms risk culture behaviours. Risk culture is assumed to be a holistic notion. The study follows a qualitative approach, yet benefits from some quantitative tools for interpretation. Accordingly, the ‘strength’ of an organisations risk culture is investigated via a five point Likert Scale questionnaire distributed to employees in Bahrain’s financial and non-financial industries. The study finds that financial and non-financial institutions in Bahrain require similar developments to foster a risk-aware culture. Both industries leave the vaster regional and societal culture to influence employees perceptions. Bahrain’s institutions need to reconsider their risk management tools and models, promote a learning culture, and place great efforts to deviate themselves from the Middle Eastern misconceived notion that culture cannot be cultivated to support organisational goals.